Turning the World Upside Down: Gender and Inversion in the work of David Underdown - Amussen, Susan D. (History compass, 2013)
The concept of inversion, or the world turned upside down, was a central theme in the work that David Underdown produced in the second half of his scholarly career. His writing on the subject began with the subject of scolds and skimmingtons, but extended over time to the examination of Jacobean court scandals and Jacobean drama. This article examines the development of Underdown's thinking about the subject, and in particular his emerging conviction that inversion provided a way of connecting the social, cultural, and political history of early modern England. Finally, it reflects on Underdown's unfinished manuscript on the subject, and shows how the study of inversion in early modern society and culture illuminates, and is illuminated by postmodern approaches to identity, the feminist concept of patriarchal equilibrium, and recent scholarship on humor.